Absolute zero [videorecording (DVD)] - Dugan, David; Dugan, David; Ross, Neil, 1944-; Shachtman, Tom, 1942- (WGBH Boston Video, 2007)
Presents the history of low-temperature research and the quest for ever-lower notches on the thermometer. The conquest of cold opens with experiments in the 1600s that asked what heat and cold are and whether they are different aspects of the same phenomenon. Shows how the experiments that settled those questions helped stoke the Industrial Revolution. The race for absolute zero dramatizes the rivalry between Scottish researcher James Dewar and Dutch physicist Heike Onnes, who plunged cold science to the forbidding realm at which oxygen and then hydrogen turn into liquids. Shows how the quest continues today as scientists pioneer super-fast computing near absolute zero--the ultimate chill of -459.67° F, where atoms slow to a virtual standstill.